Translation and Validation of a Filipino Version of the Children’s Visual Function Questionnaire - James Abraham B. Lee, MD; Andrea Kristina F. Monzon-Pajarillo, MD; Alvina Pauline D. Santiago, MD (Philippine Journal of Ophthalmology)
Objective: The objectives of this study were to translate into Filipino the Children’s Visual Function Questionnaire for children 3 years and above (CVFQ3plus), and to validate the translated CVFQ3plus to be used locally to assess the quality of life (QoL) of Filipino children aged 3 to 7 years old with visual impairment.